Effects of Starch Synthesis-Related Genes Polymorphism on Quality of Glutinous Rice - Zhang, Ouling; Liang, Cheng; Yang, Bowen; You, Hui; Xu, Liang; Chen, Yongjun; Xiang, Xunchao (Frontiers in Plant Science, 2021)
Glutinous rice qualities include gel consistency (GC), thermal characteristics and pasting viscosity property, etc., because of no amylose. However, their genetic network regulation of different quality indices has not been systematically studied. The aim was to carry out genetic diversity studies and investigated the genetic relationship between starch synthesis-related genes (SSRGs) and the physicochemical properties of glutinous rice by association analysis. The genotypes of 17 SSRGs were analyzed using 47 gene-specific molecular markers in 63 glutinous rice accessions. Targeted-gene association analysis and gene interactions analysis indicated that soluble starch synthase (SS) II-3, SSI, starch branching enzyme (SBE)4, and pullulanase (PUL) had significant genetic effects on the eating and cooking qualities (ECQs). SSI and SSII-3 were the major genes that regulated thermal properties and retrogradation properties. PUL was central in the regulation of GC, and it participated in the regulating of pasting viscosity parameters except for pasting time and pasting temperature. SBE3, ISA, SSIV-2, SBE4, SSIV-1 and their interaction with SSII-3 regulated gelatinization temperature and pasting viscosity parameters. The starch properties of glutinous rice are mainly controlled by SSII-3, SSI, PUL, and their interaction, but SSII-3 is based on centre. These findings indicate that starch properties in glutinous rice have a complex genetic system. It provides crucial information for promoting ECQs of glutinous rice.